Otonomi Daerah dan Negara Federasi - ali zavi; reny yulianti (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2018)
Option to apply the idea of ​​autonomy as broad as possible, autonomy special, and federation alike can be expected to answer a wide range the problems facing the Indonesian nation as it is today. But which option the best should be seen in the context of the nation's needs we are today. Therefore, let us not be absolute and moreover threatening each other as if a republican boat would break if the unitary state transformed into a federation or if defended furiously as a country unity. Let these choices be widely understood, new then people are ready to set a rational choice. In view authors of both the Unitary State and the Federated States both contain strengths and weaknesses. Therefore, the first must get attention is about the guarantee of justice that can grow and flourish in in one of the two forms of the state, and the second is a matter guarantee national integration to address the national disintegration symptoms broke out lately.